2021
DOI: 10.37989/gumussagbil.667592
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinin Ekip Çalışmasına Yönelik Tutumları, Profesyonel Değerleri ve Etkileyen Faktörler: Tanımlayıcı Bir Çalışma

Abstract: Hemşirelik öğrencilerinin ekip çalışmasına yönelik tutumları ve profesyonel değerler düzeyleri bakım kalitesini etkileyen önemli bir etmendir. Bu çalışmanın amacı hemşirelik öğrencilerinin ekip çalışmasına yönelik tutumları, profesyonel değerleri ve etkileyen faktörleri belirlemektir. Çalışmanın evrenini 2018-2019 yıllarında bir üniversitenin hemşirelik bölümüne devam eden öğrenciler oluşturmuştur (N=460). Çalışmanın evrenini araştırmanın yapıldığı dönemde derslere aktif katılan ve araştırmaya katılmayı kabul … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
3
Order By: Relevance
“…This result can be explained by the fact that most students have taken courses related to basic health and mental health fields and are aware of this issue. In a study conducted to evaluate the mental health literacy and psychological resilience levels of 268 students enrolled in the undergraduate departments of a health-themed foundation university, the mean score of students' mental health literacy was 16.60±2 (Polat Olca 2023). In a study conducted to determine the mental health literacy levels of health professionals (nurses, dieticians, midwives, health officers, biologists, social workers, and child development specialists), the mean total score obtained from the MHLS scale was found to be 16.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by the fact that most students have taken courses related to basic health and mental health fields and are aware of this issue. In a study conducted to evaluate the mental health literacy and psychological resilience levels of 268 students enrolled in the undergraduate departments of a health-themed foundation university, the mean score of students' mental health literacy was 16.60±2 (Polat Olca 2023). In a study conducted to determine the mental health literacy levels of health professionals (nurses, dieticians, midwives, health officers, biologists, social workers, and child development specialists), the mean total score obtained from the MHLS scale was found to be 16.…”
Section: Discussionmentioning
confidence: 99%
“…KZÖ toplam puan ve cinsiyet ile ilişkisine baktığımızda; kadınların üst biliş, erkeklerin ise biliş seviyesinin anlamlı olarak daha yüksek olduğu ve araştırmaya katılan çoğu öğrencinin de kadın olduğu belirlenmiştir. Sağlık alanı ve dışında öğrencilerle yapılan çalışmalara bakıldığında; katılımcıların çoğunluğunu kadınların oluşturduğu belirtilmiştir (Uludağ ve Deveci, 2018;Koçak ve Özdemir, 2015). Bizim bulgumuzun aksine, erkek öğrencilerin KZÖ toplam puanını daha yüksek bulan çalışmalar da bulunmaktadır (Abaslı ve Polat, 2019;Uludağ ve Deveci, 2018).…”
Section: Bulgular Ve Tartişmaunclassified
“…Sağlık alanı ve dışında öğrencilerle yapılan çalışmalara bakıldığında; katılımcıların çoğunluğunu kadınların oluşturduğu belirtilmiştir (Uludağ ve Deveci, 2018;Koçak ve Özdemir, 2015). Bizim bulgumuzun aksine, erkek öğrencilerin KZÖ toplam puanını daha yüksek bulan çalışmalar da bulunmaktadır (Abaslı ve Polat, 2019;Uludağ ve Deveci, 2018). Cinsiyetin kültürel değişkenleri etkilemediğini gösteren çalışma da bulunmaktadır (Okuyan, 2019).…”
Section: Bulgular Ve Tartişmaunclassified
See 1 more Smart Citation
“…Cao et al (2020) determined that during the pandemic, 24.9% of university students were worried about the disease, and 0.9% had severe anxiety (Cao et al, 2020). Okuyan et al (2020) reported that nursing students had high levels of anxiety during the pandemic, they were negatively affected by staying at home, they felt nervous and overwhelmed, and had fear of infection and death and suggested that their concerns should be identified (Birimoğlu Okuyan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%